2021
DOI: 10.1101/2021.01.21.427665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual expression of Atoh1 and Ikzf2 promotes transformation of adult cochlear supporting cells into outer hair cells

Abstract: Mammalian cochlear outer hair cells (OHCs) are essential for hearing. OHC degeneration causes severe hearing impairment. Previous attempts of regenerating new OHCs from cochlear supporting cells (SCs) had yielded cells lacking Prestin, a key motor protein for OHC function. Thus, regeneration of Prestin+ OHCs remains a challenge for repairing OHC damage in vivo. Here, we reported that successful in vivo conversion of adult cochlear SCs into Prestin+ OHC-like cells could be achieved by simultaneous expression of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
(139 reference statements)
0
10
0
Order By: Relevance
“…In contrast, Ikzf2 is specifically and permanently expressed in OHCs, and expression patterns of Ikzf2 and Prestin have perfect overlap. Moreover, it has been shown that ectopic Ikzf2 in IHCs can derepress Slc26a5 50,52 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, Ikzf2 is specifically and permanently expressed in OHCs, and expression patterns of Ikzf2 and Prestin have perfect overlap. Moreover, it has been shown that ectopic Ikzf2 in IHCs can derepress Slc26a5 50,52 …”
Section: Discussionmentioning
confidence: 99%
“…Historically, besides cochlear OHCs, Prestin has been considered to be expressed in vestibular HCs, 47,48 but this is not supported by analyzing two knockin mouse strains Slc26a5 YFP /+ and Slc26a5 CreER /+ 23,24 . Recently, Prestin has been reported to be additionally expressed in cardiomyocytes, 49 but paradoxically, Slc26a5 DTR /+ mice treated with diphtheria toxin, survived 50 . Although such controversies are not yet completely resolved, we speculated that Slc26a5 is exclusively turned on in cochlear OHCs at perinatal ages, then permanently maintained afterward while being repressed or expressed at very low levels in other tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atoh1 has been the focus of studies on HC development and regeneration since the importance of this gene was discovered 16,27,37,38,44 ; however, which cochlear cell lineages express Atoh1 has remained widely debated because distinct assays or mouse models have yielded divergent or contradictory results. The transgenic Atoh1Cre+ model supports that Atoh1 is also expressed in SGNs, 31 whereas Atoh1 is not detected in SGNs of Atoh1 Cre/+ knockin strains 45 .…”
Section: Introductionmentioning
confidence: 99%